Submillisecond folding of monomeric lambda repressor. - Huang, G S (1995)
The folding kinetics of a truncated form of the N-terminal domain of phage lambda repressor [lambda 6-85] has been investigated by using the technique of dynamic NMR. lambda 6-85 has been shown previously to fold in a purely two-state fashion. This allows the determination of folding and unfolding rates from simulation of the exchange-broadened aromatic resonances of Tyr-22. The folding kinetics were determined over a range of 1.35 to 3.14 M urea. The urea dependence of both folding and unfolding rate constants is exponential, suggesting that the rate-determining step is invariant at the urea concentrations studied. The folding and unfolding rates extrapolated to 0 M urea at 37 degrees C are 3600 +/- 400 s-1 and 27 +/- 6 s-1, respectively. The observed lambda 6-85 folding rate constant exceeds that of other fast-folding globular proteins by a factor of 14-54. The urea dependence of the folding and unfolding rate constants suggests that the transition state of the rate-determining step is considerably more exposed to solvent than previously studied protein-folding transition states. The surprising rapidity of lambda 6-85 folding and unfolding may be the consequence of its all-helical secondary structure. These kinetic results clearly demonstrate that all of the fundamental events of protein folding can occur on the submillisecond time scale.